Misconstructing Pseudo-Complement Clauses and Extraposition in English Writing by Elementary Students: A Cognitive Syntax Lens - Stevani, Margaret; Wijayati, Wahyu; Taufik, Taufik; Saragi, Alexander Adrian (Journal of English Language and Education, 2025)
This research examined systematic errors in pseudo-complement clauses and extraposition. The errors included subject-raising issues, verb-complement mismapping, nominalization drift, and filler-gap confusion. These were found in the English writing of Indonesian elementary school students in Medan, North Sumatra and Manado, North Sulawesi. The research used a cognitive syntax framework and applied a qualitative multiple-case study design. Data were collected through free-writing prompts. The findings revealed frequent clause misformations. Common patterns included overuse of “It is + Verb + That/To” constructions, blending of that/to clauses, mislearned subject raising, and poor control of nonfinite clauses. These errors reflected deeper cognitive struggles. Students had difficulty managing clause control, syntactic focus, and verb-complement alignment. The issues were partly influenced by L1 transfer and rote use of lexical chunks. Many students tried to express abstract ideas without sufficient syntactic mastery. These were not isolated mistakes, but signs of developing syntactic representation. The research emphasized the need for clause-based instruction. Such instruction can support both conceptual understanding and grammatical development. The implications for early writing pedagogy and future developmental studies in bilingual contexts were also discussed